Cacao (Theobroma cacao) Production Forecasting in Lampung Province with the Double Exponential Smoothing Method - Ana Risqa JL; Tuti Maryani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cacao (Theobroma cacao) is one of the Indonesian plantation commodities which can be processed into cacao and chocolate products which contain natural antioxidants. In Lampung, the cacao commodity is very superior because every year it has significantly increased and cocoa production is one of the plantation commodities that has contributed to the export development of Lampung Province. In this case, forecasting can be used to estimate that cacao production will always experience an increase or decrease. Another function is to provide information for farmers and the government. Forecasting uses the Double Exponential Smoothing method because the technique is suitable for forecasting with trend patterns and for the long term. The results and discussion of this research is that cacao production has increased in forecasting for 10 years with good MAPE criteria, namely 10.81484. From the discussion above, forecasting cocoa production using the Exponential Smoothing method, namely the Double Exponential Smoothing technique assisted by R software, is suitable for use because it produces good forecasts and a low forecasting accuracy value.